2021
DOI: 10.1186/s13027-021-00379-y
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics in hepatic metastasis by colorectal cancer

Abstract: Background Radiomics is an emerging field and has a keen interest, especially in the oncology field. The process of a radiomics study consists of lesion segmentation, feature extraction, consistency analysis of features, feature selection, and model building. Manual segmentation is one of the most critical parts of radiomics. It can be time-consuming and suffers from variability in tumor delineation, which leads to the reproducibility problem of calculating parameters and assessing spatial tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 64 publications
0
38
0
Order By: Relevance
“…In the last decade there has been growing consensus regarding the role of breast parenchyma as an independent risk factor for breast cancer [4][5][6]: consequently, a number of approaches to breast parenchyma assessment have been proposed, among which radiomic texture feature extraction is the most spread [7][8][9]. Radiomics is an emerging field and has a keen interest, especially in the oncology field [10][11][12]: it has been shown that radiomics could be predictive of TNM grade, histological grade, response to therapy and survival in various tumors [13][14][15]. Textural radiomic features of breast parenchyma have been shown to be useful for cancer classification, too [16].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade there has been growing consensus regarding the role of breast parenchyma as an independent risk factor for breast cancer [4][5][6]: consequently, a number of approaches to breast parenchyma assessment have been proposed, among which radiomic texture feature extraction is the most spread [7][8][9]. Radiomics is an emerging field and has a keen interest, especially in the oncology field [10][11][12]: it has been shown that radiomics could be predictive of TNM grade, histological grade, response to therapy and survival in various tumors [13][14][15]. Textural radiomic features of breast parenchyma have been shown to be useful for cancer classification, too [16].…”
Section: Introductionmentioning
confidence: 99%
“…Radiomic features provide data on tumor phenotype as well as cancer microenvironment. Radiomics-derived parameters, when associated with other clinical pertinent data and correlated with outcomes data, can produce accurate robust evidence-based clinical-decision support systems (CDSS) [25][26][27][28][29][30][31][32]. The possibility to connect radiological and clinical data in the present SR template could create the basis for a large database, allowing not only epidemiological statistical analyses, but also the building of radiomics models [29].…”
Section: Discussionmentioning
confidence: 99%
“…The "Clinical Evaluation" section collected previous examinations findings, a genetic panel, results of histopathological examination on biopsy specimen, chromogranin A (CgA) level, neuronspecific enolase (NSE) level, 5-hydroxyindoleacetic acid (5-HIAA) 24-h urine level, serum gastrin level, serum insulin level, serum glucagon level, serum VIP level, blood count, serum creatinine, liver function and clinical symptoms. This data could serve as a basis for creating potentially large databases, allowing not only for epidemiological statistical analysis, but also for building a radiomics model through the combination of radiological features and clinical data (24)(25)(26)(27)(28)(29). To this end, genomic data could also be leveraged to build a radiogenomics model, which may be useful in the upper levels of personalised risk stratification and advanced precision medicine for early cancer diagnosis, cancer therapy selection, prognosis prediction, and assessment of treatment response and resistance to therapy (30)(31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%